Indirectly Activated Treg Allow Dominant Tolerance to Murine Skin-grafts Across an MHC Class I Mismatch After a Single Donor-specific Transfusion. Issue 7 (July 2020) - Zhang, Geoff Yu; Hu, Min; Watson, Debbie; Wang, Yuan Min; Knight, John F.; Alexander, Stephen I.
Abstract : Background: Tolerance induced in stringent animal transplant models using donor-specific transfusions (DST) has previously required additional immunological manipulation. Here, we demonstrate a dominant skin-allograft tolerance model induced by a single DST across an major histocompatibility class I mismatch in an unmanipulated B6 host. Methods: C57BL/6 (H-2 b ) (B6) mice were injected intravenously with splenocytes from B6.C.H-2 bm1 (H-2k bm1 ) (bm1) or F1 (B6 × bm1) mice before skin transplantation. Mice were transplanted 7 days postinjection with donor (bm1 or F1) and third-party B10.BR (H-2 k ) skin grafts. Results: B6 hosts acutely rejected skin grafts from B6.C.H-2 bm1 (bm1) and F1 (B6 × bm1) mice. A single transfusion of F1 splenocytes into B6 mice without any additional immune modulation led to permanent acceptance of F1 skin grafts. This graft acceptance was associated with persistence of donor cells long-term in vivo . The more rapid removal of DST bm1 cells than F1 cells was reduced by natural killer-cell depletion. Tolerant grafts survived an in vivo challenge with naive splenocytes. Both CD4 + CD25 + and CD4 + CD25 − T cells from F1 DST treated B6 mice suppressed alloproliferation in vitro . Tolerance was associated with expansion of peripheral Foxp3 + CD4 + CD25 + regulatory T cells (Treg) and increased forkhead box P3 (Foxp3) expression in tolerant grafts. In tolerant mice, Foxp3 + Treg arises from the proliferation of indirectly activated natural Foxp3 + Treg (nTreg) and depletion of Foxp3 + Treg abrogates skin-graft tolerance. Conclusions: This study demonstrates that the persistence of transfused semiallogeneic donor cells mismatched at major histocompatibility class I can enhance tolerance to subsequent skin allografts through indirectly expanded nTreg leading to dominant tolerance without additional immunological manipulation.